2017
DOI: 10.1155/2017/4627905
|View full text |Cite
|
Sign up to set email alerts
|

Acute Hematogenous Osteomyelitis in a Five-Month-Old Male with Rickets

Abstract: Osteomyelitis is defined as an infection of the bone, bone marrow, and the surrounding soft tissues. Most cases of acute hematogenous osteomyelitis in children are caused by Gram-positive bacteria, principally Staphylococcus aureus. We present a case where a 5-month-old male had an acute onset of decreased movement of his left leg and increased irritability and was subsequently diagnosed with rickets and hematogenous osteomyelitis with bacteremia. The case explores a possible association between hematogenous o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Previously, John et al described an infant with osteomyelitis, who had nutritional rickets caused by vitamin D deficiency. 18 Maier et al found that vitamin D deficiency was severe in patients with periprosthetic joint infection, recognizing vitamin D as an important mediator of immune function and it may have a preventive role in the pathogenesis of periprosthetic joint infection. 19 Moreover, osteomyelitis is less common in developed countries than in developing countries, 18 where although there may be less sun exposure, there are also fewer nutritional deficits.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, John et al described an infant with osteomyelitis, who had nutritional rickets caused by vitamin D deficiency. 18 Maier et al found that vitamin D deficiency was severe in patients with periprosthetic joint infection, recognizing vitamin D as an important mediator of immune function and it may have a preventive role in the pathogenesis of periprosthetic joint infection. 19 Moreover, osteomyelitis is less common in developed countries than in developing countries, 18 where although there may be less sun exposure, there are also fewer nutritional deficits.…”
Section: Discussionmentioning
confidence: 99%
“…18 Maier et al found that vitamin D deficiency was severe in patients with periprosthetic joint infection, recognizing vitamin D as an important mediator of immune function and it may have a preventive role in the pathogenesis of periprosthetic joint infection. 19 Moreover, osteomyelitis is less common in developed countries than in developing countries, 18 where although there may be less sun exposure, there are also fewer nutritional deficits. So, in patients with rickets, we should be aware of a possible increased risk of bone or joint infection.…”
Section: Discussionmentioning
confidence: 99%
“…Rickets also reduces the body immune and the child become more susceptible to infectious disease especially osteomyelitis as stated by John and colleagues. 13…”
Section: Discussionmentioning
confidence: 99%
“…11 There is an association between rickets and some infectious diseases like hematogenous osteomyelitis in children. 13 In the differential diagnosis of different forms of rickets; the detailed family history, physical examination, biochemical assessment and X-ray imaging are required. 11,2 This study aimed to find the characteristics of rickets at JafarIbn Auf pediatric hospital in Sudan.…”
Section: Introductionmentioning
confidence: 99%